Future wealth - Davis, Stanley M.; Meyer, Christopher 1948- (Harvard Business School Press, 2000)
The authors argue that wealth accumulation is shifting from income that is earned (salaries) to unearned (investments). They show how the current shift from computing to communicating will alter the process of wealth creation, accumulation, control and distribution.